2018
DOI: 10.1007/s11252-018-0799-x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding performance of an apex predator, the peregrine falcon, across urban and rural landscapes

Abstract: Urban environments present wildlife with major challenges and yet surprising numbers of species have colonised towns and cities globally. Despite the growing realisation that urban centres can be important habitats for wildlife, why some species do better than others in urban environments remains poorly understood. Here, we compare the breeding performance of an apex predator, the peregrine falcon (Falco peregrinus), in urban and rural environments, and test whether variation in reproductive success between an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 74 publications
0
33
0
2
Order By: Relevance
“…Key aspects for the successful establishment of an urban raptor population are the availability of nest sites and prey [109]. A similarly comprehensive study on the breeding performance of peregrines across urban and rural landscapes [31] suggested that higher prey density in urban areas was the main driver of higher productivity (in terms of breeding success, the number of young fledged in successful nests, and overall productivity including nest failures) in these habitats. However, information detailing breeding phenology-which proved to be a key mechanism for higher productivity in peregrines in our work-was not incorporated in their study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Key aspects for the successful establishment of an urban raptor population are the availability of nest sites and prey [109]. A similarly comprehensive study on the breeding performance of peregrines across urban and rural landscapes [31] suggested that higher prey density in urban areas was the main driver of higher productivity (in terms of breeding success, the number of young fledged in successful nests, and overall productivity including nest failures) in these habitats. However, information detailing breeding phenology-which proved to be a key mechanism for higher productivity in peregrines in our work-was not incorporated in their study.…”
Section: Discussionmentioning
confidence: 99%
“…First, for specialised predators of birds, city centres can be a source of high prey abundance [30]. This has been quantified in other studies of urban raptors [82], including peregrines in the United Kingdom [31], where avian prey density was found to be higher in urban breeding territories than at rural sites; and Black Sparrowhawks (Accipiter melanoleucus) in Cape Town [19], where higher densities of many avian prey species were found in modified landscapes and urban areas than in more natural habitat types. In urban environments, the diet of peregrines typically consists of relatively few species, particularly pigeons and doves (Columbidae), and passerines (thrushes Turdidae and starlings Sturnidae; [83,84]).…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…In Britain, built-up areas host twenty percent of the blackbird, starling and song thrush populations and significant numbers of other species (Gregory and Baillie 1998). Species such as peregrine falcons are choosing to become urban specialists, attracted by the nesting-site potential of tall buildings and ready food supply of feral pigeons (Kettel et al 2019). Further, targeted conservation efforts have prompted increases in urban populations of some bat species (Hayhow et al 2016).…”
Section: The Solution: Rewilding Our Citiesmentioning
confidence: 99%